Mythic Discourses - Frog; Siikala, Anna-Leena; Stepanova, Eila (2012)
"Mythic discourses in the present day show how vernacular heritage continues to function and be valuable through emergent interpretations and revaluations. At the same time, continuities in mythic images, motifs, myths and genres reveal the longue durée of mythologies and their transformations. The eighteen articles of Mythic Discourses address the many facets of myth in Uralic cultures, from the Finnish and Karelian world-creation to Nenets shamans, offering multidisciplinary perspectives from twenty eastern and western scholars. The mythologies of Uralic peoples differ so considerably that mythology is approached here in a broad sense, including myths proper, religious beliefs and associated rituals. Traditions are addressed individually, typologically, and in historical perspective. The range and breadth of the articles, presenting diverse living mythologies, their histories and relationships to traditions of other cultures such as Germanic and Slavic, all come together to offer a far richer and more developed perspective on Uralic traditions than any one article could do alone."